Does raising the retirement age increase employment of older workers? - Stefan Staubli; Josef Zweimüller (Institute for the Study of Labor (IZA), 2011)
This paper studies how an increase in the minimum retirement age affects the labor market behavior of older workers. Between 2000 and 2006 the Austrian government gradually increased the early retirement age from 60 to 62.2 for men and from 55 to 57.2 for women. Using administrative data on the universe of Austrian private-sector employees, the results from the empirical analysis suggest that this policy change reduced retirement by 19 percentage points among affected men and by 25 percentage points among affected women. The decline in retirement was accompanied by a sizeable increase in employment of 7 percentage points among men and 10 percentage points among women, but had also important spillover effects into the unemployment insurance program. Specifically, the unemployment rate increased by 10 percentage points among men and 11 percentage points among women. In contrast, the policy change had only a small impact on the share of individuals claiming disability or partial retirement benefits.
urn:nbn:de:101:1-201107283912
Keywords: J14; J26; 330; early retirement; retirement age; labor supply; policy reform